Indonesia’s deregulated generation expansion planning model based on mixed strategy game theory model for determining the optimal power purchase agreement - Budi, Rizki Firmansyah Setya; Sarjiya, Sarjiya; Hadi, Sasongko Pramono (Elsevier, 2022)
Obtaining the optimal power purchase agreements (PPA) in deregulated generation expansion planning is crucial. A lower PPA provided by the utility results in the independent power producer (IPP) becoming disinterested in investment. On the other hand, a higher PPA increases the government’s financial burden. Therefore, this study proposes a generation expansion planning model that considers the deregulated market and PPA determination. A game theory based on a mixed strategy method and bi-level model is used in this research. To obtain the PPA optimum value, a multi-scenario analysis is conducted by changing the PPAs from 25% to 100% of the generation cost. The proposed model is applied to the Bangka Belitung power system. The results of the multi-scenario analysis show that the optimum PPA is 30% of Bangka Belitung’s generation cost. This PPA creates an optimum generation expansion planning with a levelized elec- tricity cost of 6.009 cents USD/kWh. However, the utility cannot offer a PPA of less than 30% of the generation cost because the private sector is not interested in investing. Therefore, it forces the utility to rent diesel power plants and increases the LCOE to 8.629 cents USD/kWh.